2017
DOI: 10.1242/jcs.200659
|View full text |Cite
|
Sign up to set email alerts
|

Unphosphorylated STAT1 represses apoptosis in macrophages during Mycobacteriumt uberculosis infection

Abstract: In murine macrophages infected with Mycobacterium tuberculosis (Mtb), the level of phosphorylated STAT1 (P-STAT1), which drives the expression of many pro-apoptosis genes, increases quickly but then declines over a period of hours. By contrast, infection induces a continued increase in the level of unphosphorylated STAT1 that persists for several days. Here, we found that the level of unphosphorylated STAT1 correlated with the intracellular bacterial burden during the later stages of infection. To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 68 publications
(93 reference statements)
2
23
0
Order By: Relevance
“…Similarly, the expression of miR-27b was upregulated, and the endogenous expression of Bag2 was inhibited post-H37Ra infection, suggesting that M. tuberculosis-induced overexpression of miR-27b is associated with the inhibition of Bag2. Furthermore, recent studies have shown that Bag2 binds to Sp110 (a positive anti-mycobacterial regulator) (45) and unphosphorylated STAT1 (46) to alter the cell death pathway. These results indicate a critical role of Bag2 in modulating macrophage resistance to M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the expression of miR-27b was upregulated, and the endogenous expression of Bag2 was inhibited post-H37Ra infection, suggesting that M. tuberculosis-induced overexpression of miR-27b is associated with the inhibition of Bag2. Furthermore, recent studies have shown that Bag2 binds to Sp110 (a positive anti-mycobacterial regulator) (45) and unphosphorylated STAT1 (46) to alter the cell death pathway. These results indicate a critical role of Bag2 in modulating macrophage resistance to M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, Yao et al recently observed in Mycobacterium tuberculosis (Mtb)-infected macrophages a rapid increase in phosphorylated STAT1, which quickly declined over a period of hours, but a continued increase of unphosphorylated U-STAT1 that persisted for several days. As such, U-STAT1 affected the expression of several immune-associated genes, and lowered sensitivity of macrophages to CD95-mediated apoptosis during Mtb infection ( 54 ). Likewise, Majoros et al showed the importance of U-STAT1 in IFN-I-induced gene expression regulation and biological activity in mice expressing a Stat1Y701F mutant ( 19 ).…”
Section: Unphosphorylated Stat1 and Stat2: U-isgf3 U-stat2/irf9 Andmentioning
confidence: 99%
“…Nevertheless, IFN-α has been consistently reported to selectively induce proinflammatory genes containing GAS in the absence of an ISRE [63][64][65][66][67]. Moreover, it has recently been evidenced that U-STAT1 persists in macrophages following pathogenic stimulation it and could induce immunomodulatory genes, in contrast to phosphorylated (p)-STAT1, which undergoes rapid degradation [68].…”
Section: Introductionmentioning
confidence: 99%